2022
DOI: 10.3389/fphar.2022.878749
|View full text |Cite
|
Sign up to set email alerts
|

Caper (Capparis spinosa L.): An Updated Review on Its Phytochemistry, Nutritional Value, Traditional Uses, and Therapeutic Potential

Abstract: Caper (Capparis spinosa L.) is a perennial shrub of the family Capparaceae, endemic to circum-Mediterranean countries. Caper carries a renowned nutritional value, especially in terms of vitamins and antioxidants related to the occurrence of flavonoids, alkaloids, and glucosinolates as main secondary metabolites. Caper extracts have also shown to display antibacterial, antifungal, analgesic, antitumor, hepatoprotective, antioxidant, anti-inflammatory, and neuroprotective effects which correlate the uses of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 103 publications
0
12
0
Order By: Relevance
“…Since ancient times, medicinal and aromatic plants have been recognized as reliable sources of health-promoting bioactive agents and a valuable source for finding new drug leads ( Kicel, 2020 ; Annaz et al, 2022 ). Recently, several serious concerns have been raised about the quality, efficacy, and safety of synthetic drugs ( Sahoo et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since ancient times, medicinal and aromatic plants have been recognized as reliable sources of health-promoting bioactive agents and a valuable source for finding new drug leads ( Kicel, 2020 ; Annaz et al, 2022 ). Recently, several serious concerns have been raised about the quality, efficacy, and safety of synthetic drugs ( Sahoo et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, many research investigations were devoted to the anticancer potential of the plant. The toxicity of different phytochemicals against tumor cell lines is mainly due their capacity to suppress many pro-oncogenic pathways and genes and to stimulate tumor suppressor-like pathways ( 125 ). Moreover, elicitation of proapoptotic proteins and impairment of mitochondrial membrane potential could also be targeted by plant compounds ( 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, our study showed antioxidative activity along with lipid control and protection against liver enzymes. The phytochemical analysis also revealed the presence of flavonoids among others that forms the basis for antioxidative activities [ 49 ] and lipid regulation for future studies. In addition to flavonoids, the phytochemical analysis also revealed the presence of alkaloids, flavonoids, and phenols that cause to mitigate the cytotoxic effects of intoxication-derived free radicals.…”
Section: Discussionmentioning
confidence: 99%